1983
DOI: 10.1111/j.1745-9125.1983.tb00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Detention Patterns of Successful and Unsuccessful Insanity Defendants

Abstract: ABSTRACT* * * This study examines the detention patterns of the insanity defendant who is successful with the plea and hospitalized, or unsuccessful and incarcerated. Further comparisons are made with felony defendants who never entered a plea of not guilty by reason of insanity (NGRI). From existing data it is unclear to what extent detention may vary if the plea is successful as compared to if it is not successful. Of all defendants who entered a plea of NGRI in Erie County, New York (Buffalo) between 1970 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…Several studies have found that the nature of the index offense is correlated with the duration of detention for individuals found NCRMD (Braff, Arvanites, & Steadman, 1983;Harris, Rice, & Cormier, 1991;Silver, 1995). Research with both inmates and forensic patients has also consistently demonstrated that the number of previous convictions is positively correlated with recidivism (Quinsey, Harris, Rice, & Cormier, 1998), resulting in criminal history and prior violence being common variables in established violence risk assessment measures (e.g., HCR-20, Webster, Douglas, Eaves, & Hart, 1997).…”
Section: Criminal Variablesmentioning
confidence: 99%
“…Several studies have found that the nature of the index offense is correlated with the duration of detention for individuals found NCRMD (Braff, Arvanites, & Steadman, 1983;Harris, Rice, & Cormier, 1991;Silver, 1995). Research with both inmates and forensic patients has also consistently demonstrated that the number of previous convictions is positively correlated with recidivism (Quinsey, Harris, Rice, & Cormier, 1998), resulting in criminal history and prior violence being common variables in established violence risk assessment measures (e.g., HCR-20, Webster, Douglas, Eaves, & Hart, 1997).…”
Section: Criminal Variablesmentioning
confidence: 99%
“…Several studies have found that the nature of the index offense is correlated with the duration of detention for individuals found NCRMD (Braff, Arvanites, & Steadman, ; Harris, Rice, & Cormier, ; Silver, ). Research with both inmates and forensic patients has also consistently demonstrated that the number of previous convictions is positively correlated with recidivism (Quinsey, Harris, Rice, & Cormier, ), resulting in criminal history and prior violence being common variables in established violence risk assessment measures (e.g., HCR‐20, Webster, Douglas, Eaves, & Hart, ).…”
Section: What Predicts Success or Failure On Conditional Discharge?mentioning
confidence: 99%
“…If the arguments regarding insanity are not persuasive, then raising the defense could make a guilty verdict more likely. Braff, Arvanites, and Steadman (1983) conducted a study on all defendants who entered a plea of NGRI in an upstate New York county over a 10‐year period to determine if there were discrepancies in the detention patterns between successful and unsuccessful insanity defendants. The study sample included 202 insanity defendants, of whom 25.2% were found NGRI, 65.8% pled guilty or were convicted, 1% were acquitted, and 7.9% had their charges dropped.…”
Section: Knowledge Of the Insanity Defensementioning
confidence: 99%
“…The study sample included 202 insanity defendants, of whom 25.2% were found NGRI, 65.8% pled guilty or were convicted, 1% were acquitted, and 7.9% had their charges dropped. In addition, they compared the length of imprisonment between unsuccessful insanity defendants and defendants who never raised the plea, and found that unsuccessful NGRI defendants were incarcerated 22% longer than those who did not raise the plea (Braff et al, 1983). This finding demonstrates that defendants who plead insanity may be punished for raising the defense by receiving longer sentences.…”
Section: Knowledge Of the Insanity Defensementioning
confidence: 99%